Weekly Sediment Yield Dynamic Model for Naula Watershed of Ramganga Reservoir - Pyasi, S K; Singh, J K (Journal of Agricultural Engineering, 2001)
The linear and non-linear weekly sediment yield prediction models based on concept of determining and assigning the varying weightages to the antecedent events of runoff and sedimentation were developed for the Naula watershed of Ramganga reservoir. These antecedent events of runoff and sediment were found to have significant impact on the present day yield of sediment. The weights determined for three successive antecedent events, affecting the current event, came out to be 44.84%, 32.13% and 23.03%, respectively. Only active weeks data were used for development of the first and the second set data models. The weekly linear dynamic models were not found suitable for the study due to very low value for RÂ². However, the value for RÂ² for the first and the second data set nonlinear sediment yield prediction model were found equal to 77% and 74%, respectively. The first and the second data set models were developed by considering the active data for 1973-83 and 1988-1992, respectively. Both these models were found performing well within the permissible limits of qualitative parameters for 3-4 years ahead prediction of sediment yield to be contributed to Ramganga reservoir.